Penyertaan Modal “PEMDA” Pada Badan Usaha Milik Daerah (BUMD) - Djumardin - (Jatiswara, 2015)
One of the duties of Newmont Nusa Tenggara Ltd. as stipulated in the article 24 of contract work is to divest gradually the share up to 51%. Such share shall be distributed either to government (central or local government), private enterprise or government enterprise. Since it spends huge budget to purchase the share, then the local government of West Nusa Tenggara through consortium among Provincial Government of West Nusa Tenggara, District Government of Sumbawa and District Government of West Sumbawa establish Daerah Maju Bersaing Ltd. cooperating with private enterprise Multi Capital Ltd. as capital provider have succeed to do acquisition 24% of the share of Newmont Nusa Tenggara Ltd.